The biodiverse rotifers (Rotifera: Eurotatoria) of the floodplain wetlands of Barak valley of Assam, Northeast India - Sharma, Bhushan Kumar (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2019)
The present analysis of alpha diversity of Rotifera of the floodplain wetlands of Barak valley, south Assam, northeast India (NEI) reveals 170 species, belonging to 39 genera and 19 families, with three species new to the Indian sub-region and two species new to Assam state. The rich and diverse rotifer assemblages comprise ~70%, ~57% and ~39% of total species of the Phylum known till date from Assam, NEI and India, respectively and thus affirm habitat and ecological heterogeneity of the Barak River floodplain wetlands. The elements of global biogeographic importance include one Australasian, eight Oriental, 10 Paleotropical, one Indo-Chinese, one cosmo (sub) tropical and four other species, and ~37% species merit regional distribution interest for India with ~13% exclusively reported from NEI. Lecanidae (~30%) and Brachionidae ≈ Lepadellidae (~32%) largely contribute to the rotifer richness; Trichocercidae > Testudinellidae are notable (~15%), and Notommatidae, Euchlanidae, Mytilinidae, Trichotriidae and Trochosphaeridae collectively form 16.5%. Lecane is the most speciose genus; Lepadella > Brachionus = Trichocerca include ~32% species, while Testudinella > Keratella deserve mention. Rotifera of the Barak floodplains exhibit the littoral-periphytonic nature, several small sized species and tropical character.